Pengaruh Literasi Pasar Modal terhadap Keputusan Berinvestasi pada Mahasiswa Program Studi Akuntansi Universitas Persatuan Guru 1945 NTT - Andreas Hati; Made Susilawati; Dwi Dersmi Selan (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study is to determine the effect of capital market literacy on investment decisions among students of the Accounting Study Program at Universitas Persatuan Guru 1945 NTT, from 2024 to 2025. In this study, the author employed a quantitative approach, with primary data collected through questionnaires from a population and sample of 16 respondents who are active investors at Universitas Persatuan Guru 1945 NTT. The analytical technique used was simple linear regression analysis to partially calculate the effect of capital market literacy (X) on investment decisions (Y) among student respondents from the Accounting Study Program at Universitas Persatuan Guru 1945 NTT. The results of this study indicate that capital market literacy has a positive or significant effect on investment decisions among students of the Accounting Study Program at Universitas Persatuan Guru 1945 NTT. This is demonstrated by the t-table value of 2.131, which represents the critical t-table limit, while the t-calculated value is 4.961 with p = 0.000, < 0.05, and the investment decision result is Y = 11.049 + 0.528 X, meaning that hypothesis Ha1 is accepted, whereby capital market literacy has a positive or significant effect on investment decisions. Meanwhile, the coefficient of determination (r²) test result is 0.637, which means that 63.7% of the variation in investment decisions can be explained by capital market literacy. The remaining 36.3% is explained by other variables not included in this study's variables.